Local Economic Development Policies - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2003)
This chapter seeks to provide useful advice for local government policy towards economic development programs. The chapter: reviews the size and scope of local economic development programs in the United States; critically analyzes the various rationales offered for these programs; makes recommendations for what local policy should do about business attraction and incentives, business retention, new business development, high technology development, brownfield development, distressed neighborhoods, and downtowns; and discusses how local economic development programs should be organized, managed, and evaluated.
Additional information: A revised version of this paper appears as "Economic Development" in J. Richard Aronson and Eli Schwartz, eds. 2004. Management Policies in Local Government Finance (5th Ed.). Washington, DC: International City/County Management Association, pp. 355-390.
Keywords: R58; R38; R11; R23; 330; local; regional; economic; development; Bartik